2009
DOI: 10.1093/toxsci/kfp266
|View full text |Cite
|
Sign up to set email alerts
|

In Utero and Lactational Exposure to Bisphenol A, In Contrast to Ethinyl Estradiol, Does Not Alter Sexually Dimorphic Behavior, Puberty, Fertility, and Anatomy of Female LE Rats

Abstract: Many chemicals released into the environment display estrogenic activity including the oral contraceptive ethinyl estradiol (EE2) and the plastic monomer bisphenol A (BPA). EE2 is present in some aquatic systems at concentrations sufficient to alter reproductive function of fishes. Many concerns have been raised about the potential effects of BPA. The National Toxicology Program rated the potential effects of low doses of BPA on behavior and central nervous system (CNS) as an area of "some concern," whereas mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
107
3
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(120 citation statements)
references
References 66 publications
8
107
3
2
Order By: Relevance
“…This study shows no effects on male offspring regarding anogenital distance, age at puberty, morphology of external genitalia, areolae/nipple retention, reproductive organ weights and sperm numbers (Howdeshell et al, 2008). Also in female offspring, no effects on anogenital distance, age at puberty, morphology of external genitalia or fecundity were reported (Ryan et al, 2010a). The latter study also addressed specifically the impact of BPA on the sexually dimorphic behaviour of female rats, i.e.…”
Section: Reproductive and Developmental Toxicitymentioning
confidence: 66%
See 3 more Smart Citations
“…This study shows no effects on male offspring regarding anogenital distance, age at puberty, morphology of external genitalia, areolae/nipple retention, reproductive organ weights and sperm numbers (Howdeshell et al, 2008). Also in female offspring, no effects on anogenital distance, age at puberty, morphology of external genitalia or fecundity were reported (Ryan et al, 2010a). The latter study also addressed specifically the impact of BPA on the sexually dimorphic behaviour of female rats, i.e.…”
Section: Reproductive and Developmental Toxicitymentioning
confidence: 66%
“…In this section only in vivo studies fully compliant with the selection criteria set in section 3 "Introduction" (PART II) are addressed. To meet the request of the Danish Minister for Food, Agriculture and Fisheries, in this section also the studies by Ryan et al (2010a) and Howdeshell et al (2008) in female and male rats, respectively, of the same reproductive toxicity study are addressed (see section 5.2.1.1). EFSA Journal 2010; 8(9):1829 5.2.1.1.…”
Section: Reproductive and Developmental Toxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…It is noteworthy that two preeminent reproductive biologists who have made highly significant contributions to this field have developed scepticism on the claimed effects for BPA. Ryan and co-workers 60 showed that BPA did not alter sexually dimorphic behaviour, puberty, fertility or anatomy of female LongEvans rats, which contradicted prior results or conclusions drawn by other groups. In a commentary, Sharpe, 61 a coauthor of the initial endocrine disruptor hypothesis, clearly answered in the affirmative the title of his highlight 'Is it time to end concerns over the estrogenic effects of BPA?'.…”
Section: Conclusion and Surprisesmentioning
confidence: 77%